Control of trichome formation in Arabidopsis by poplar single-repeat R3 MYB transcription factors - Zhou, Limei; Zheng, Kaijie; Wang, Xiaoyu; Tian, Hainan; Wang, Xianling; Wang, Shucai (Frontiers in Plant Science, 2014)
In Arabidopsis, trichome formation is regulated by the interplay of R3 MYBs and several others transcription factors including the WD40-repeat protein TRANSPARENT TESTA GLABRA1 (TTG1), the R2R3 MYB transcription factor GLABRA1 (GL1), the bHLH transcription factor GLABRA3 (GL3) or ENHANCER OF GLABRA3 (EGL3), and the homeodomain protein GLABRA2 (GL2). R3 MYBs including TRICHOMELESS1 (TCL1), TRYPTICHON (TRY), CAPRICE (CPC), ENHANCER OF TRY AND CPC1 (ETC1), ETC2 and ETC3 negatively regulate trichome formation by competing with GL1 for binding GL3 or EGL3, thus blocking the formation of TTG1-GL3/EGL3-GL1, an activator complex required for the activation of the trichome positive regulator gene GL2. However, it is largely unknown if R3 MYBs in other plant species especially woody plants have similar functions. By BLASTing the Populus trichocarpa protein database using the entire amino acid sequence of TCL1, an Arabidopsis R3 MYB transcription factor, we identified a total of eight R3 MYB transcription factor genes in poplar, namely Populus trichocarpa TRICHOMELESS1through 8 (PtrTCL1-PtrTCL8). The amino acid signature required for interacting with bHLH transcription factors and the amino acids required for cell-to-cell movement of R3 MYBs are not fully conserved in all PtrTCLs. When tested in Arabidopsis protoplasts, however, all PtrTCL interacted with GL3. Expressing each of the eight PtrTCLs genes in Arabidopsis resulted in either glabrous phenotypes or plants with reduced trichome numbers, and expression levels of GL2 in all transgenic plants tested were greatly reduced. Expression of PtrTCL1 under the control of TCL1 native promoter almost completely complemented the mutant phenotype of tcl. In contrast, expression of PtrTCL1 under the control of TRY native promoter in the try mutant, or under the control of CPC native promoter in the cpc mutant resulted in glabrous phenotypes, suggesting that PtrTCL1 functions similarly to TCL1, but not TRY and CPC.